Peran Apoteker Dalam Program Berhenti Merokok: Systematic Review - Aivi Yola Dwiputri; Dedy Almasdy; Almahdy A (Journal of Pharmaceutical and Sciences, 2023)
Smoking is one of the most important health problems causing an increase in cardiovascular disease, lung disease, and cancer in the world. It is known that cigarettes have killed nearly 7 million people in the world. To deal with this, pharmacist have a very important role and are responsible for providing education to the community. The purpose of this study was to identify the role of pharmacist in smoking cessation programs. This study uses a systematic review method where 10 articles from 815 articles that meet the criteria are found, with a search string from 2012 to 2023. The results of this study indicate that the role of pharmacist in smoking cessation programs includes education, giving advice, invitations to quit smoking and nicotin replacement therapy. However, the role of pharmacist in smoking cessation programs is still not optimal due to limited competence and low confidence in success.